Pengaruh Inflasi, Nilai Tukar, dan BI 7 Day Repo Rate terhadap Return Saham pada Industri Barang Konsumsi di Indeks Saham Syariah Indonesia (ISSI) Tahun 2017-2020 - Sultoni, Mohammad Hamim; Nisa, Khoirun (Shafin: Sharia Finance and Accounting Journal, 2022)
This study aims to determine the effect of inflation, exchange rates, BI 7 Day Repo Rate on stock returns in the consumer goods industry in the Indonesian Sharia Stock Index (ISSI) in 2017-2020 partially or simultaneously, using purposive sampling, the sample used is 25 companies. , using a quantitative approach in the form of secondary data, with multiple linear regression analysis found that the results of research on inflation, exchange rates, and the BI 7 Day Repo Rate have a significant effect on stock returns simultaneously or partially.